2013
DOI: 10.1073/pnas.1222041110
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase-activated fluorophores for rapid discrimination of mycobacterial species and strains

Abstract: Most current diagnostic tests for tuberculosis do not reveal the species or strain of pathogen causing pulmonary infection, which can lead to inappropriate treatment regimens and the spread of disease. Here, we report an assay for mycobacterial strain assignment based on genetically conserved mycobacterial sulfatases. We developed a sulfatase-activated probe, 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one)-sulfate, that detects enzyme activity in native protein gels, allowing the rapid detection of sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 51 publications
3
58
0
1
Order By: Relevance
“…Other peptide sequences can be incorporated into the synthesis scheme to create catalyCEST MRI contrast agents that sense other proteases (26). Other classes of enzymes that modify an aryl functional group may also be detected using this platform technology, such as esterases (7), phosphatases (27), and sulfatases (28). The salicylic acid moiety may be replaced by other molecules that have intramolecular hydrogen bonding that causes highly shifted CEST signals and are less likely to undergo slow degradation (11,17,29).…”
Section: Discussionmentioning
confidence: 99%
“…Other peptide sequences can be incorporated into the synthesis scheme to create catalyCEST MRI contrast agents that sense other proteases (26). Other classes of enzymes that modify an aryl functional group may also be detected using this platform technology, such as esterases (7), phosphatases (27), and sulfatases (28). The salicylic acid moiety may be replaced by other molecules that have intramolecular hydrogen bonding that causes highly shifted CEST signals and are less likely to undergo slow degradation (11,17,29).…”
Section: Discussionmentioning
confidence: 99%
“…[6] We recently reported on the use of fluorogenic probes to examine mycobacterial sulfatase activity in a variety of species and strains. [7] In that work, we developed a new fluorogenic probe, 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one)(DDAO)-sulfate, which was used to detect sulfatase activity in protein gel-resolved mycobacterial lysates. The assay revealed that mycobacteria have distinct sulfatase activity patterns, or “fingerprints”.…”
mentioning
confidence: 99%
“…DDAO has also been conjugated to form activatable fluorophores through conjugation of its hydroxyl group resulting in photoactivatable and sulfatase activatable probes. 42, 43 …”
Section: Resultsmentioning
confidence: 99%